Efektivitas Layanan Informasi yang Mengkombinasikan Metode Ceramah, Sosiodrama, dan Diskusi dalam Merubah Persepsi Siswa Tentang Disiplin Belajar - Sudirman, Afrizal; Mudjiran, Mudjiran; Rusdinal, Rusdinal (Universitas Negeri Padang, 2015)
The students misperception about learning discipline had triggered the students to break the rules applied at school. They seemed to be unaware of the nature of learning discipline so that an affort to change their perception was needed. One of the efforts done to change the students perception was by applying information service. This research was intended to see the affectiveness of information service combined with lecturing method, socio-drama and discussion to change the students perception about learning discipline. Based on the research findings, it was concluded that the use of information service combined with lecturing method, socio-drama, and discussion was affective to change the students perception about learning discipline. The research applied quantitative method. This was a Quasi Experimental research which applied The Non Equivalent Control Group. The population of this research was the students at SMAN 8 Padang. The sample was chosen by using Purposive Sampling Technique. The instrument of the reseach Likert scale model. The data gathered were analyzed by using Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Independent Sample assisted with SPSS version 17. The results showed that information service combined with lecturing method, socio-drama, and discussion was affective to change the students perception about learning discipline.